Resistance calculation and operational parameter optimization of anopener based on dynamic friction characteristics test of bulk materials - Yang, Renqiang; Guan, Zhengjun; Zhang, Lihua; Xu, Yuanhang (International Journal of Agricultural and Biological Engineering, 2024)
Currently, friction characteristics obtained from empirical parameters or soil direct shear tests are widely applied in the resistance calculation and operational parameter optimization of soil tillage components. However, the operation of soil-touching components is a dynamic process, and there are few reports on the dynamic friction characteristics of soil-contacting components in agricultural tillage based on factors such as different moisture content, pressure, and relative velocity. Herein, a test device to measure the friction characteristics of compressible bulk materials was developed: the interface friction between the soil and 65Mn plate and the internal friction characteristics of soil were tested using this device, and the dynamic changes of interface friction coefficient and internal friction coefficient with moisture content, pressure, and relative velocity were obtained. Based on the dynamic friction parameters of soil, the ditching resistance model of a typical ploughshare opener was established, the ditching resistance value was predicted, and field experiments were performed under different operating speeds (0.5 m/s, 0.7 m/s, and 0.9 m/s) and ditching depths (60 mm, 100 mm, and 140 mm). The results indicated that the calculated values of the ditching resistance model based on the dynamic friction parameters of soil reduced the error by 15% compared with the calculated values based on the friction characteristics of the soil direct shear test, which verified the accuracy of the ditching resistance model and the validity of the parameters obtained from the test device for the friction characteristics of compressible bulk materials. In addition, the minimum ditching resistance can be obtained when the ditching speed is 0.7 m/s at the same ditching depths, which is consistent with the dynamic friction characteristics of soil. It can be found that the dynamic friction characteristics of bulk materials have basic theoretical support for the optimization of operational component structures and operational parameters.Keywords: bulk materials, dynamic friction characteristics, ditching resistance model, operational parameter optimizationDOI: 10.25165/j.ijabe.20241706.9297Citation: Yang R Q, Guan Z J, Zhang L H, Xu Y H. Resistance calculation and operational parameter optimization of anopener based on dynamic friction characteristics test of bulk materials. Int J Agric & Biol Eng, 2024; 17(6): 121–130.